Induction Coil Heating Improves the Efficiency of Insect Olfactory Studies - Yang, Liu; Liu, Yuzhe; Richoux, Gary M.; Bernier, Ulrich R.; Linthicum, Kenneth J.; Bloomquist, Jeffrey R. (Frontiers in Ecology and Evolution, 2019)
Electroantennography (EAG) is a commonly used method to study the olfactory responses of insects, but many behaviorally relevant odorant responses are difficult to evaluate because only a small amount of chemical sample is available in the vapor phase. We have assembled a coupled induction heating-electroantennogram (IH-EAG) system to improve the release efficiency of tested compounds. This system allows precise temperature control from room temperature to 600 C of the carbon steel wire without changing significantly the air delivery temperature to the antennae. After heating to 135 C (wire temperature read by a calibrated thermocouple), EAG response to 0.1 mg of DEET increased from 0.11 to 0.33 mV, which is not significantly different from the EAG response to 1 mg at room temperature (ca. 25 C). Likewise, response to 1-octen-3-ol was detected at 0.1 mg after heating to 135 °C and was equivalent to 1 mg at room temperature. For the low volatility compound VUAA-1, an experimental insect repellent, the EAG response increased 60-fold, from 0.16 to 9.52 mV after heating to 500 C without degradation of the sample, as determined by NMR. Overall, this system can easily reduce the amount of chemical used in an EAG assay up to 10-fold and provided the compound is not thermally labile, allows for rapid testing of slow acting, less volatile compounds for eliciting an olfactory response from insects or other animals.